Immunomodulatory effects of intratumoral cowpea mosaic virus and calreticulin nanoparticles in canine tumors: early results - Singh, Akansha; Affonso de Oliveira, Jessica Fernanda; Schrader, Jessica; Kishore, Deepan; Chandrasekar, Sri Vidhya; Fiering, Steven; Steinmetz, Nicole F.; Ranjan, Ashish (Frontiers in Immunology, 2025)
IntroductionIntratumoral immunotherapy delivers immune-modifying therapeutic agents directly into the tumor microenvironment (TME), stimulating both local and systemic immune responses. In this pilot study, we evaluated the immunomodulatory effects of cowpea mosaic virus (CPMV) particles, which primarily activates innate immunity, and calreticulin nanoparticle (CRT-NP), which enhance immunostimulatory signals of immunogenic cell death in canine cancers. The study focused on their potential to induce local and systemic antitumor immune responses and achieve tumor control.MethodCPMV was obtained through the mechanical inoculation of Vigna unguiculata, while CRT-NP was generated using cationic liposomes loaded with a CRT-expressing plasmid. Nine canine patients with oral melanoma, soft-tissue sarcoma (STS), and mammary gland carcinoma received CPMV or CRT-NP via intratumoral route. CPMV and CRT-NP was administered weekly at three-five intratumoral locations. To evaluate antitumor immune responses, biopsies and blood samples were obtained prior to treatment and during follow-up visits, extending up to one week after the final treatment. Endpoints included serum cytokine analysis, tumor transcriptomics via NanoString, immune cell profiling in blood and tumor biopsies, and efficacy assessment using RECIST criteria.ResultCPMV exhibited an icosahedral shape ( 30 nm), while CRT-NP were spherical ( 300 nm). CPMV induced stable disease (SD) in two of three melanoma and STS patients, with partial response (PR) in the third. CRT-NP induced SD in two of three patients, with one STS patient achieving partial remission. Post-treatment NanoString and flow cytometry analyses revealed a shift in the tumor microenvironment toward a more immunostimulatory state, marked by increased neutrophils and CD8+ T cells. CPMV, in particular, upregulated genes involved in antigen processing and immune activation while enhancing IFNγ+ CD4+ and CD8+ T cell populations. CRT-NP reduced Tregs in the TME. Further, serum cytokine levels, such as MCP-1, GM-CSF, IL-2, IL-6, IL-7 and IL-18, correlated with tumor growth independent of various treatments.DiscussionOur findings suggest that CPMV and CRT-NP, which activate distinct immunologic pathways, safely modulate the TME contributing to disease stabilization in spontaneous canine cancers. These results support the need for larger-scale trials to address current limitations, differentiate tumor-agnostic versus treatment-specific effects, and evaluate long-term clinical outcomes, including overall survival (OS).